(untitled) (Journal of Medical & Health Sciences Review, 2023)
Precision oncology represents a paradigm shift in cancer treatment by tailoring therapies to the unique genetic makeup of individual tumors. This approach leverages advanced molecular profiling techniques to identify actionable mutations within cancer cells, enabling the selection of targeted drugs that exploit these vulnerabilities for more effective and less toxic treatment. This article explores the key principles and applications of precision oncology, highlighting its potential to improve patient outcomes and transform cancer care. Keywords Precision oncology, targeted therapy, personalized medicine, cancer genomics, molecular profiling, biomarker analysis, drug resistance, clinical trials